A Comparative Analysis of Resource Utilization using ISO/IEC 25010 in REST API File Upload Testing: Postman (GUI-Based) and Cucumber (Code-Based) - Thooriqoh, Hazna At; Mulyo, Budi Mukhamad; Rakhmadi, Ardhon (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
To guarantee quality and dependability, testing of REST Application Programming Interfaces (APIs) is an essential part of contemporary software development cycles. However, with a multitude of available testing frameworks, selecting the most efficient tool for specific tasks, such as file uploads, remains a challenge. The decision often overlooks the critical factor of resource utilization, which can significantly impact system performance and cost, particularly in continuous integration environments. This study addresses this problem by providing a comparative analysis of resource utilization between two popular REST API testing frameworks, Postman (GUI-based) and Cucumber (code-based), specifically for a file upload transaction. The research utilizes relevant metrics from the ISO/IEC 25010 standard, which cover processor, memory, I/O, storage, and bandwidth. The findings reveal that while Cucumber exhibits superior bandwidth efficiency, Postman demonstrates more significant efficiency in all other key resource metrics. Quantitatively, Postman's processor utilization was found to be approximately 74% lower, and its memory usage around 80% lower than that of Cucumber. These findings provide crucial empirical evidence for software developers and testers, enabling them to make informed decisions on tool selection based on specific resource efficiency priorities for file upload transactions.